Immunoglobulin G4‐related disease in a dog - Lydia J. Colopy; Kai‐Biu Shiu; Laura A. Snyder; Anne C. Avery; Emily D. Rout; A R. Moore (Journal of Veterinary Internal Medicine, 2019)
Abstract Immunoglobulin G4‐related disease (IgG4‐RD), which affects many organ systems, has been recognized as a distinct clinical entity in human medicine for just over a decade but has not been previously identified in dogs. In humans, IgG4‐RD is characterized by diffuse IgG4‐positive lymphoplasmacytic infiltrates that commonly lead to increased serum concentrations of IgG4 and IgE, peripheral eosinophilia, tumorous swellings that often include the parotid salivary glands, obliterative phlebitis, and extensive fibrosis. Herein we describe the diagnosis, clinical progression, and successful treatment of IgG4‐RD in an 8‐year‐old female spayed Husky mixed breed dog. Immunoglobulin G4‐related disease should be considered as a differential diagnosis for dogs with vague clinical signs, lymphoplasmacytic swellings, restricted polyclonal gammopathy, eosinophilia or some combination of these findings.